Evaluation of Polyphenols, Vitamin C Contents and Antioxidant Activity of Two Types of Algerian Honey - Necib, A; Ketfi, L; Draiaia, R; Rezig, S. (My University, 2022)
This study aimed to estimate two different types of Algerian honey: antioxidant contents (total phenols and vitamin C), and levels of antioxidant (DPPH assay) and reducing activity (FRAP assay). Honey samples were characterized by high content of total phenols (314.231 ± 281.346 – 394.231 ± 155.835 mg AG 100 g-1) and low vitamin C values (0.25 ± 0.05 – 0.35 ± 0.05 mg 100 g-1). As a result, the antioxidant activity and reducing capacity values were found to be 9.578 ± 3.157 and 11.255 ± 2.668% for DPPH and 15.240 ± 4.578 to 17.794 ± 8.179 μg 100 g-1 for the FRAP assay. Our data showed that dark honey contains bioactive compounds with significant antioxidant activity